Amplified Decoupling in the Global Economy: The Case of Bilateral Investment Treaties - Nina Bandelj; Aaron Tester (Socius, 2020)
Developing countries adopt global policies in their quest for economic development. Studies show that such policies are decoupled from their intended effects, or that over time, they become more effective. But what if the opposite happens and policies, which were initially efficacious, become increasingly decoupled with time? We recognize this phenomenon as amplified decoupling. Combining historical and quantitative analysis, we examine a case of bilateral investment treaties (BITs), established to protect and promote foreign direct investment (FDI). The influence of BITs on FDI is significant in the early periods but becomes weaker over time. Historical analysis reveals the unexpected role of (post)communist countries in using BITs for geopolitical purposes and highlight the impact of international organizations which broker treaty signing among pairs of developing countries engaged in economic diplomacy. We suggest that amplified decoupling can result because of institutional multivalence, whereby practical actors reframe and repurpose policies toward uses that were originally unintended.